First records of the genera Neocylloepus and Pilielmis (Coleoptera: Elmidae: Elminae) from Venezuela, with the description of Pilielmis shepardi sp. nov. - Polizei, Thiago T. S.; Barclay, Maxwell V. L. (Zootaxa, 2019)
Neocylloepus Brown, 1970 and Pilielmis Hinton, 1971 are Neotropical genera of riffle beetles, mainly distributed in Central America and the north of South America. These genera are here reported for the first time from Venezuela, and a new species, Pilielmis shepardi sp. nov. is described and illustrated. The type material is housed in Museu de Zoologia da Universidade de São Paulo, São Paulo, Brazil (MZSP), Natural History Museum, London, UK (BMNH), Museo del Instituto de Zoología Agrícola, Maracay, Venezuela (MIZA), Michael A. Ivie Collection, Bozeman, Montana, USA (MAIC), and National Museum of Natural History, Smithsonian Institution, Washington DC, USA (USNM).